Echocardiographic guidance for HARPOON beating-heart mitral valve repair. (23rd June 2021) - Gackowski, Andrzej; D'Ambra, Michael N; Diprose, Paul; Szymański, Piotr; Duncan, Alison; Bartus, Krzysztof; Gammie, James S
Abstract: The HARPOON mitral valve (MV) repair system has been shown to safely and effectively treat a degenerative MV prolapse with transventricular implantation of artificial cords on a beating heart. The low profile system is introduced and precisely steered under 3D TEE guidance towards the previously selected target on a prolapsing MV segment. It allows puncture and deployment of a knot on the leaflet. The procedure is repeated until desired number of knots are implanted and the cords are optimally tensioned to restore coaptation. The cords are then tied down on the epicardium over a felt pledget. State of the art echocardiographic imaging is a crucial part of the procedure. It starts from patients screening, pre-procedural analysis and planning, access selection, navigation, deployment, optimal cordal tensioning, and final MV assessment and is continued during the follow-up assessment. This article illustrates the specific echocardiographic aspects of the HARPOON procedure including 2D and advanced 3D TEE techniques. The echocardiographic protocol was developed based on initial experience in 60 procedures. Detailed training of the echocardiographer and surgical team, is mandatory to achieve excellent results of this procedure, being now introduced in the clinical practice. Graphical Abstract: